Pengaruh Lama Fermentasi EM4 Pada Tepung Daun Ubi Jalar (lpomea batatas) Sebagai Bahan Baku Tambahan Pelet Ikan Gurame (Osphronemus gourami) - Abdurrasyid; Dewi Putri Lestari (Agroinovasi: Jurnal Ilmu dan Teknologi Pertanian, 2024)
The purpose of this study was to analyze the effect of the best EM4 fermentation time on sweet potato leaf flour (I. batatas) as an additional raw material for fish pellets in the cultivation of gourami (O. gourami), To obtain the best EM4 fermentation time on sweet potato leaf flour (l. batatas) as an additional raw material for fish pellets in the cultivation of osphronemus gourami (O. gourami). The method used in this study was an experimental method. The research design used was a Completely Randomized Design (CRD) using 3 treatments and 5 replications. The treatments tried were the addition of sweet potato leaf flour with different EM4 fermentation times. The conclusion of this study is that the fermentation time on sweet potato leaf flour using EM-4 microorganism solution has been shown to reduce crude fiber and increase protein in sweet potato leaf flour. The best fermentation time is 14 days of fermentation, the crude fiber content is lower and the protein is higher compared to the fermentation time of 7 days.